Mabel Meed at the wheel of the steamboat PROSPECTOR during a trip up the Pelly River, Yukon Territory, 1905. - University of Washington Libraries. Special Collections Division
PH Coll 246.202 [Meed journal: "My wife at wheel of "Prospector", Pelly River trip."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number